Sentiment Analysis using Opinion Mining on Customer Review - Prachiti Akre; Rushikesh Malu; Aparna Jha; Yash Tekade; Wani Bisen (International Journal of Engineering and Management Research, 2023)
Opinion mining is the process of discovering user opinions about a subject, a product, or an issue. Sentiment analysis is the process of separating opinions' feelings from those opinions. This work presents a comprehensive review of techniques in sentiment analysis using opinion mining. We start by discussing the basic concepts of opinion mining and then delve into various techniques and approaches used for sentiment analysis. This work focuses on analyzing the user reviews on products from e-commerce websites such as amazon.com and compares products of similar specifications based on the polarity of user reviews for the products calculated using nlp and naive bayes classification.